Evaluation of the match external load in soccer: methods comparison - Castagna, C.; Varley, M.; Póvoas, S. C. A.; D`Ottavio, S. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To test the interchangeability of 2 match-analysis approaches for external-load detection considering arbitrary selected speeds and metabolic power (MP) thresholds in male top-level soccer.